1971
DOI: 10.1136/bmj.4.5785.460
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngological Aspects of Sjogren's Syndrome

Abstract: Epistaxis, soreness and dryness of the throat, dysphagia, and hoarseness were common symptoms, and rhinitis sicca and postcricoid narrowing were not uncommon features of the Sjogren groups. Oesophagoscopy in one patient revealed a web identical to that found in Paterson/Brown Kelly syndrome; none of the patients, however, had an iron-deficiency anaemia or koilonychia. There was an increased frequency of deafness in all groups, and the deafness tended to be conductive in the Sjogren groups and sensorineural in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 11 publications
1
24
2
Order By: Relevance
“…SNHL was the commonest hearing loss in our study (97 %) and this is similar to other studies reviewed from published literature [10,16,17]. Doig et al's study [23] is the only study reporting conductive hearing loss in their patients (5 out of 22 pSS patients with hearing loss). Authors in that study suggested dryness of the mucous membranes of the eustachian tube and middle ear as the cause of conductive hearing loss in pSS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SNHL was the commonest hearing loss in our study (97 %) and this is similar to other studies reviewed from published literature [10,16,17]. Doig et al's study [23] is the only study reporting conductive hearing loss in their patients (5 out of 22 pSS patients with hearing loss). Authors in that study suggested dryness of the mucous membranes of the eustachian tube and middle ear as the cause of conductive hearing loss in pSS.…”
Section: Discussionsupporting
confidence: 93%
“…Tumiati et al [10] found that 9 of 14 (64.28 %) with hearing loss were asymptomatic and hearing loss was detectable only on audiometry in them. Diog et al [23] found none complaining of decreased hearing among 27 % of their patients with audiometrically documented hearing loss. In our study, a higher proportion of asymptomatic hearing loss was noted as compared to Tumiati et al [10].…”
Section: Discussionmentioning
confidence: 97%
“…Nasal crusting and epistaxis are common symptoms in SS and were reported , respectively, by 18.5% and 31.8% of patients in one series (8). Nearly one half of patients with SS in this series had nasal crusting and dryness on physical examination.…”
Section: Upper Airway Diseasementioning
confidence: 95%
“…Food fragments frequently adhere to the lips, gums and palate, requiring the patient to remove them manually. Dysphagia can be due to pharyngeal dryness, abnormal oesophageal motility [78], or a postcricoid web, the last of which may be indistinguishable, on radiographs ( Figure 6) and by oesophagoscopy [79], from that seen in the Plummer-Vinson syndrome [80,81]. Patients who develop such webs are not sideropenic and do not develop postcricoid neoplasms [2].…”
Section: Oral Manifestationsmentioning
confidence: 99%